ECOLOGICAL-GEOCHEMICAL STATE OF TOPSOIL AND WATER SEDIMENTS IN ŠIAULIAI (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Ecological-geochemical state of topsoil and water sediments in Šiauliai was evaluated taking into account total contents of 14 hazardous elements (Pb, Zn, Cu, Sn, Ag, Ni, Mo, Cr, Co, Mn, V, B, Sr, Ba) in a complex way – both according to their total contamination index and their standards (existing State standards and phytotoxic concentrations in soil used in European countries). The fraction < 1 mm of samples was analysed by atomic emission spectrophotometry. Topsoil composite samples (110 in all) were taken approximately from each square kilometre and classified into 4 groups according to functional micro-zones. The number of samples from water sediments (Talša and Ginkūnai lakes, Kulpė and Violė rivers) was 13. Even 54.5% topsoil samples were characterised by unsatisfactory final ecological-geochemical state (30% of them had bad state). Topsoil of industrial functional micro-zones had the worst state. It was followed by topsoil of residential, then by topsoil from social-residential micro-zones. Topsoil from the territories of recreation or protected areas had the best quality. Ecological-geochemical state of water sediments in Ginkūnai and Talša lakes and in Kulpė or Violė rivers was very bad or bad.